Unreported alcohol use was common but did not impact hepatitis C cure in HIV‐infected persons who use drugs. Issue 5 (7th January 2020) - Irvin, Risha; Chander, Geetanjali; Ward, Kathleen M.; Manogue, Sean; Falade‐Nwulia, Oluwaseun; Moon, Juhi; Sutcliffe, Catherine G.; Brinkley, Sherilyn; Haselhuhn, Taryn; Katz, Stephanie; Herne, Kayla; Arteaga, Lilian; et al.
Abstract: We investigated the prevalence and impact of heavy alcohol use on the hepatitis C virus (HCV) care continuum amongst HIV/HCV co‐infected persons who use drugs. In the CHAMPS study, 144 HIV/HCV co‐infected persons were randomized to contingent cash incentives, peer mentors and usual care to evaluate the impact on HCV care. Alcohol use was ascertained using the 10‐item AUDIT (hazardous: male ≥8, female ≥4) and phosphatidylethanol (PEth) (heavy: ≥50 ng/mL), an alcohol biomarker. Log binomial regression was used to evaluate the association between heavy alcohol use and failure to initiate treatment and to achieve sustained virologic response (SVR). Of the 135 participants with PEth data, median age was 55 years, 59% were male, 92% were Black, 91% reported a history of drug use, and 97% were on antiretroviral therapy. Hazardous drinking was reported on AUDIT by 28% of participants, and 35% had heavy alcohol use by PEth. Of the 47 individuals with a PEth ≥50 ng/mL, 23 (49%) reported no or minimal alcohol use by AUDIT. HCV treatment was initiated in 103 of 135 participants, and SVR was achieved in 92%. PEth ≥50 ng/mL (Relative Risk [RR] 0.72, 95% CI 0.35‐1.48) was not significantly associated with failure to initiate HCV treatment or failure to achieve SVR (RR 0.85, 95% CI 0.46‐1.57).In conclusion, alcohol use was common and frequently not detected by self‐report. However, heavy alcohol use, even when measured objectively, was not associated with failure to initiate HCV treatment or to achieve cure.